PENINGKATAN PARTISIPASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI OPERASI ALJABAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS VIII C SMP NEGERI 1 MALUNDA - Herlina Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2015)
Research using cooperative learning model of Make A Match to increase participation and learning outcomes of students showed an increase after the implementation of the action in the form of cooperative learning model of Make A Match. It seen in the percentage of students who achieve the participation of 47.38% in the first cycle, increased in the second cycle with a percentage of 80.47%. Math test results also increased, students who complete the first cycle only reaches 56.25%, while in the second cycle were able to achieve 90.625%. The results showed that the classical completeness criteria in SMP Negeri 1 Malunda, which exceeded 85% in the second cycle of learning activities. Cooperative learning model Make A Match also done well and have met the completeness criteria that have been set. From the above data, it is known that the indicators of success has been achieved, so the researchers concluded that the type of cooperative learning model of Make A Match can increase the participation and learning outcomes of learners in the learning of mathematics in the classroom followed VIII C SMP Negeri 1 Malunda.